2017
DOI: 10.1021/acs.jpcc.7b03673
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing C–C Coupling on Oxide-Derived Copper Catalysts for Electrochemical CO2 Reduction

Abstract: Copper electrodes, prepared by reduction of oxidized metallic copper have been reported to exhibit higher activity for the electrochemical reduction of CO2 and better selectivity towards C2 and C3 (C2+) products than metallic copper that has not been pre-oxidized. We report here an investigation of the effects of four different preparations of oxide-derived electrocatalysts on their activity and selectivity for CO2 reduction, with particular attention given to the selectivity to C2+ products. All catalysts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
272
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(301 citation statements)
references
References 47 publications
18
272
1
Order By: Relevance
“…The electrocatalytic activity of the Zn|ZnSO 4 (100− X ) % CuSO 4 X % electrodes for the production of syngas was investigated in a two‐compartment H‐type electrolyzer equipped with an anion exchange membrane under constant CO 2 flow (20 mL min −1 ). To limit the competitive H 2 production and explore a broader range of H 2 /CO ratios, the electrolysis was performed in 0.1 m CsHCO 3 electrolyte (pH 6.8) because previous reports demonstrated hat large cations in the electrolyte favor the reduction of CO 2 instead of protons . We used 1 cm 2 working electrodes because the properties measured on very small electrodes (<0.5 cm 2 ) do not appear to scale up correctly when increasing the geometric surface area of the electrode, likely as a consequence of the significant thickness of the deposit (≥100 μm for X≥5).…”
Section: Resultsmentioning
confidence: 99%
“…The electrocatalytic activity of the Zn|ZnSO 4 (100− X ) % CuSO 4 X % electrodes for the production of syngas was investigated in a two‐compartment H‐type electrolyzer equipped with an anion exchange membrane under constant CO 2 flow (20 mL min −1 ). To limit the competitive H 2 production and explore a broader range of H 2 /CO ratios, the electrolysis was performed in 0.1 m CsHCO 3 electrolyte (pH 6.8) because previous reports demonstrated hat large cations in the electrolyte favor the reduction of CO 2 instead of protons . We used 1 cm 2 working electrodes because the properties measured on very small electrodes (<0.5 cm 2 ) do not appear to scale up correctly when increasing the geometric surface area of the electrode, likely as a consequence of the significant thickness of the deposit (≥100 μm for X≥5).…”
Section: Resultsmentioning
confidence: 99%
“…

Oxide-derived (OD) Cu catalysts have high selectivity towards the formation of multi-carbon products (C 2 /C 3 ) for aqueous electrochemical CO 2 reduction (CO 2 R). [6][7][8][9][10][11][12][13] OD Cu catalysts are formed by oxidizing Cu and subsequently reducing it. 60 %) for up to 5hin 0.1m KHCO 3 at À1.0 Vv s. RHE.

…”
mentioning
confidence: 99%
“…The study discovered that enhancing the thickness of Cu 2 O film would lead to an increase in amount of C 2 H 4 generated and that the various Cu 2 O facets did not present any effect on the product selectivity. In fact, OD‐Cu can be shown to be selective in generating more C 2 products . A similar study further elaborated on this understanding and found out that by altering the thickness of Cu 2 O overlayer between 1.7 and 3.6 µm, it is possible to maximize the selectivity for C 2 H 4 (FE C2H4 of 34–39)% and C 2 H 5 OH (FE C2H5OH of 9–16%) at an applied potential of −0.99 V .…”
Section: Active Sites In Metal‐based Catalystsmentioning
confidence: 87%